Symmetrical Drug-Related Intertriginous and Flexural Exanthema (Sdrife) in Pediatric Patients. Case Series [Exantema Intertriginoso y Flexural Simétrico por Fármacos (Sdrife) en Pacientes Pediátricos. Serie de Casos] - Ruiz-Matus, F; Macias-Eslava, M; Pereira-Rudolph, F; Jeldres-Pulgar, A (Ediciones Doyma, S.L., 2020)
[No abstract available]